2010
DOI: 10.5056/jnm.2010.16.4.428
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxic Vomiting: A Case Report and Possible Mechanisms

Abstract: The symptoms related to gastrointestinal (GI) tract are sometimes chief complaints in patients with endocrine disease. Thyrotoxicosis is a rare, but notable cause for unexplained and repeated vomiting. Here, we report an adolescent patient with thyrotoxicosis who was initially presented with repeated vomiting and epigastric pain. A 13-year-old female was referred to a GI outpatient department for evaluation of vomiting and abdominal pain from a pediatric clinic. Esophagogastroduodenoscopy revealed acute gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…Nausea and vomiting may be associated with severe abdominal pain in some patients with thyrotoxicosis, and may result in surgical exploration [7,9,[22][23][24]. In our first two cases the patients suffered from abdominal pain, however, it was not severe as in some of the cases reported previously.…”
Section: Discussionmentioning
confidence: 41%
“…Nausea and vomiting may be associated with severe abdominal pain in some patients with thyrotoxicosis, and may result in surgical exploration [7,9,[22][23][24]. In our first two cases the patients suffered from abdominal pain, however, it was not severe as in some of the cases reported previously.…”
Section: Discussionmentioning
confidence: 41%
“…As major presenting symptoms of thyrotoxicosis, these manifestations have rarely been reported in the medical literature and have not been included as presenting symptoms of thyrotoxicosis in standard textbooks of medicine and endocrinology. [3][4][5][6][7][8][9][10][11] They are well recognized and usually seen as a presentation of thyrotoxic storm. [12][13][14] Thyrotoxic vomiting, however, was certainly known to earlier physicians, and Osler's principles and practice of medicine, vividly described such a case.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Recent literature has suggested that vomiting may be more important as a cardinal symptom of thyrotoxicosis, and that it is not only seen in thyrotoxic storm but is part of a more prolonged chronic presentation. [4][5][6][7][8][9] In most of these cases the diagnosis was delayed because of the atypical presentation of thyrotoxicosis. During pregnancy, diseases that are initially observed with vomiting as the primary symptom may be difficult to distinguish from hyperemesis gravidarum due to thyrotoxicosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased beta-adrenergic activity Increases the number of beta-adrenergic receptors 8,9 Increased thyroid hormones Stimulates the chemical trigger zone 12 Decreases gastric emptying and causes pyloric sphincter malfunction 13,14 Increases magnesium urinary excretion. Hypomagnesaemia inhibits gastric smooth muscle 15,16 Increased oestrogen level in patients of both sexes 10,12 Raised oestrogen level may induce nausea and vomiting only in susceptible patients 17 Functional duodenal obstruction Hypermotility induced volvulus of duodenal third portion has been described 18 Progress: The patient required a prolonged two weeks admission for managing her unremitting vomiting during which Propylthiouracil and Propranolol were administered via nasogastric tube.…”
Section: Mechanisms Of Thyrotoxic Vomitingmentioning
confidence: 99%